Pengaruh Perceived Organizational Support, Self Efficacy dan Lingkungan Kerja terhadap Employee Engagement Karyawan PT. Pesona Arnos Beton - David Yusuf Firnanda; Dewie Tri Wijayati (Jurnal Ilmu Manajemen, 2021)
PT. Pesona Arnos Beton is one of the organizations engaged in concrete processing, which was founded in 2016. This research aims to examine the perceived organizational support, self-efficacy, and work environment on employee engagement of employees of PT. Pesona Arnos Beton. This study is a causality study with a quantitative approach. The sampling method used was a saturated sampling method with 80 respondents. The statistical analytical used in this study was Multiple Linear Regression analytical with the help of SPSS for Windows software. The output of this research explains that perceived organizational support has a significant and positive impact on employee engagement. Self-efficacy has a significant and positive impact on employee engagement. The work environment has a significant and positive impact on employee engagement. Perceived organizational support, self-efficacy, and work environment together have a significant impact on employee engagement. Research implication that can be applied to companies is that companies need to give awards to employees who perform well. The company can provide education, training and development regularly to employees. Leaders need to impose sanctions on employees who do not wear Personal Protective Equipment. Companies also need to provide clinics or health vehicles such as ambulances to anticipate more fatal emergency events. Companies can hire motivator services to provide material and guidance to be more enthusiastic, proud, and engaged with the company.